(untitled) (Al-Academy, 2016)
In order to a chive the aim of the research the researcher chose the (Nebras kindergarten) to be the search sample .the member of the sampleFrom(males and fameless)and the researcher chose the class of(butterfly) as experimental group to do the pantomime consist of(15)males and fameless, and put(singles, senses ,double senses and communal senses)in the binging of the experiment the researcher applied the measurement of(AL Kaswany and other)as(pre_ test)which prepare to measure, the movement skills for kindergarten, the measurement have the validity and reliability to knowledge the difference between the two experiment. The experiment continue from(20/1/201to 20/2/2014)in the end of experiment the researcher applied the measurement of(AL Kaswany and others)as(post-test)the result appear more progress in pantomime, the researcher used statistical means for analysis the data in the end of experiment he recommended some recommendations